Physical examination and health assessment - Camera, Ian.; Mosby, Inc (St. Louis, MO : Elsevier/Mosby, 2012)
Covers 15 body systems with detailed video demonstrations, critical thinking cases, and NCLEX-examination review questions and a QSEN-competencies checklist. Also includes state-of-the-art medical Archie animations and documentation exercise forms
video skills -- Documentation library -- Animation library -- QSEN checklist
New to this edition are imbedded Eletronic Health Record (EHR) tied to Critical Thinking Cases and a QSEN-competencies checklist.
238 video skills -- Disk label
Includes bibliographical references and index
Minimum system requirements for Windows: Window XP SP2, or 32 bit; Window 7 operating system (64-bit versions are not currently supported. However, the application will most likely work on 64-bit version. Run as administrator may be required.); Intel Pentium 4 processor (or equivalent x86 chipset) / 1 GHz or greater; 65 MB available hard drive space; 512 MB RAM; minimum 1024 x 768 pixels screen resolution, 16-Bit color; 16x or faster CD-ROM drive / 8x or faster DVD-ROM; PDF Reader.
Minimum system requirements for Macintosh: MAC OS 10.4; Intel-based processor or PowerPC G4/G5 (867 MHz or higher); 65 MB available hard drive space; 512 MB RAM or more; 16x or faster CD-ROM drive/ 8x or faster DVD-ROM drive; Minimum 1024 x 768 pixels screen resolution; 16-Bit color, PDF reader
DVD-ROM
Keywords: Physical examination; Diagnosis; Nursing Assessment